1993
DOI: 10.1093/cvr/27.8.1482
|View full text |Cite
|
Sign up to set email alerts
|

Release of endothelin from the porcine heart after short term coronary artery occlusion

Abstract: Endothelin is released from the heart for several minutes during reperfusion following a brief coronary artery occlusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 0 publications
1
18
0
Order By: Relevance
“…3) ET-1 enhances microvascular permeability with consequent oedema resulting in microvascular compression. Our findings showed a significant increase in plasma ET-1 levels during AMI and reperfusion, which is in agreement with the report of Tønnessen [23], reflecting endothelial dysfunction caused by ischemia and reperfusion. Our findings also showed that the myocardial tissue levels of ET-1 have a significant increase in the reflow and no-reflow myocardium compared to those in the non-ischaemic myocardium, further suggesting that endothelium was damaged to some different extent in the reflow and no-reflow myocardium.…”
Section: Discussionsupporting
confidence: 93%
“…3) ET-1 enhances microvascular permeability with consequent oedema resulting in microvascular compression. Our findings showed a significant increase in plasma ET-1 levels during AMI and reperfusion, which is in agreement with the report of Tønnessen [23], reflecting endothelial dysfunction caused by ischemia and reperfusion. Our findings also showed that the myocardial tissue levels of ET-1 have a significant increase in the reflow and no-reflow myocardium compared to those in the non-ischaemic myocardium, further suggesting that endothelium was damaged to some different extent in the reflow and no-reflow myocardium.…”
Section: Discussionsupporting
confidence: 93%
“…This view is supported by the observation that NOS inhibitor (L-NMMA) exhibited no effect on adenosine-induced dilation in the previous study. 3 It is speculated that the increased release of local endothelin, as commonly observed in myocardial ischemia, [35][36][37][38] may contribute to the selective endothelial dysfunction related to NO deficiency. In the present study, we found that the dilation of collateral-dependent arterioles to smooth muscle K ATP channel activator pinacidil was not altered (supplemental Figure IA), suggesting the lack of effect of coronary occlusion on endothelium-independent dilation of coronary arterioles to adenosine.…”
Section: Thengchaisri Et Al Exercise Restores Coronary Arteriolar Dilmentioning
confidence: 99%
“…Evidence suggests that the endothelins might be important modulators of both vascular tone and myocardial contractility following myocardial infarction (Yasuda et al, 1990;Watanabe et al, 1991;Matsuyama et al, 1991;T0nnessen et al, 1993). In addition, endothelins may be involved in the development of cardiac hypertrophy.…”
Section: Calculation Of Binding Parametersmentioning
confidence: 99%